Synthesis and optimization of waste treatment flowsheets - Linninger, Andreas A.; Chakraborty, Aninda (Computers & chemical engineering, 1999)
This paper proposes pharmaceutical waste management through computer-aided synthesis of treatment policies composed of reuse, recycle and recovery options for valuable raw materials and chemically reactive methods for the destruction of offending species. Synthesis of a comprehensive superstructure, which embeds all feasible treatment alternatives, will be demonstrated as a linear planning problem. Combinatorial complexity is tackled by means of an operation representation that features both logical as well as non-linear functional transition models. In step two, rigorous optimization reveals the optimal treatment policy. Plant-wide optimal policies reach regulatory compliance at minimal cost and satisfy site-specific constraints such as limited availability of treatment processes, bounded yearly emission thresholds, or desired level of material recovery. Computer-aided waste management also provides assessment of costs and benefits associated with pollution prevention efforts. The proposed hybrid methodology may be used for conceptual screening of technologies in situations where size and complexity of the problem space escapes purely rigorous methods.